Skate kitchen [videorecording (DVD)] - Moselle, Crystal; Vinberg, Rachelle; Smith, Jaden, 1998-; Adams, Kabrina (Magnolia Home Entertainment, 2018)
Camille is an introverted eighteen-year-old skateboarder who lives on Long Island with her single mother. She discovers "The Skate Kitchen", a subculture of girls whose lives revolve around skating, and bravely seeks them out. The rambunctious big-city girls quickly adopt the naive Camille as part of their gang. However, she soon learns the complexity of friendship when she befriends a boy (Smith) from a rival group of skaters.